Optimalisasi Peran Komunikasi Dan Disiplin Kerja Dalam Meningkatkan Kinerja Karyawan Fia Decoration Ponorogo - Sofia Kharimatul Mubarokah; Fery Setiawan (Jurnal Pengabdian Manajemen, 2023)
Human resources are the company's most important assets and are needed by the company to achieve the goals of the company. This research is the result of lecture academic activities at the study program level, namely the Independent Work Report (LKM). The object of this research is a service company named Fia Decoration. In the Fia Decoration company, human resources play an important role in achieving the goals of the company. There are several indications of problems that exist within Fia Decoration, namely communication between employees and work discipline. Researchers are trying to create a simple solution method in the form of joint gymnastics and coffee together. These two activities aim to improve the principles of communication and work discipline of all employees. The result of this activity is that the enthusiasm of the employees in participating in joint gymnastics and drinking coffee together is quite good, so that communication and work discipline are better.